Penerapan Strategi Pembelajaran Langsung dalam Meningkatkan Keterampilan Prosedural Siswa - Annisa’ Fitri; Sherilla Nava Angel Gea; Gusmaneli (La-Tahzan: Jurnal Pendidikan Islam, 2024)
ABSTRAK: This research is based on problems that arise may Focus on the effectiveness of implementing direct learning strategies in improving students' procedural skills. This could include questions about how well the strategy is implemented, the extent to which the student is improving in skill procedures. The purpose of this assessment is to train students on procedural skills in direct learning strategies. as well as declarative knowledge that is well structured and can be taught step by step. The type of research used is classroom action research which aims to overcome problems in the classroom, namely improving students' procedural skills. Based on the research results obtained in these journals, implementing direct learning strategies to improve students' procedural skills can increase student motivation in learning and can improve student learning outcomes. Based on the results of the review of these articles, it is clear that the application of direct learning strategies improves students' procedural skills during the learning process by giving questions to students and also looking at students' skills in solving questions based on predetermined procedures.